GEOLOGICAL FACTORS AND PHYSICOCHEMICAL PROCESSES OF GROUNDWATER FORMATION IN THE TUNKA DEPRESSION - S. Kh. Pavlov; K. V. Chudnenko; V. A. Golubev; A. I. Orgilyanov; P. S. Badminov; I. G. Kryukova (Геодинамика и тектонофизика, 2018)
The article describes the complex hydrogeological conditions of the Baikal rift zone viewed as a large structural element and pioneers in distinguishing two independent hydraulic systems in the study area. Groundwater resources and compositions of groundwater in these two systems are generated in fundamentally different ways. In the deep sediment layers, groundwater generated due to sedimentation is at the stage of elision (exfiltration) water exchange. Active phase transition of clay minerals to hydromica causes an additional water release, and sedimentary water and regenerated groundwater infiltrate from the condensed clay strata to sandy horizons. This process is accompanied by decompaction, heaving sand, and high (extra-high) reservoir pressures. Nitrogen-rich water and carbonic thermal water associated with faults and fault nodes are widespread in the basement of the Tunka depression. The thermal water result from infiltration and, together with fresh water, represents a uniform hydraulic system. Its development is determined by the dynamics of infiltration water in the water-feeding area in the Tunka loaches. At different hypsometric levels of the hydrogeological section, nitrogen-rich water descends, while carbonic thermal water ascends, and these processes occur simultaneously. Our study is focused on the physicochemical processes of the interaction between groundwater and sedimentary and crystalline rocks. It shows that the ion-salt and gas compositions of not only nitrogen-rich thermal water, but also those of methane water and carbonic thermal water occur in the ‘water-rock’ system without involving any additional substance from external sources. Compared to other thermal water, the composition of carbonic water is formed in a more complex way: first, it goes through the stage of the nitrogen-rich thermal water while passing through the aluminosilicate rocks and only then interacts with the carbonate rocks and become carbonic. The formation of carbonic water is accompanied by intensive karst processes at depths, which are ceasing closer to the surface. As a result of degassing, an opposite process is activated: authigenic minerals and travertines are formed on the surface. Groundwater and its gas phase are involved in the formation of rocks with a negative temperature, which are abundant in the Tunka depression, as well as large positive forms of the relief. It is shown that the activity of groundwater is not limited to the role of a filler in the host rocks and an intermediary medium between different geospheres. Groundwater is an active agent that initiates, controls and implements many geological processes.